2014
DOI: 10.1007/s11433-014-5612-0
|View full text |Cite
|
Sign up to set email alerts
|

High precision landing site mapping and rover localization for Chang’e-3 mission

Abstract: This paper presents the comprehensive results of landing site topographic mapping and rover localization in Chang'e-3 mission. High-precision topographic products of the landing site with extremely high resolutions (up to 0.05 m) were generated from descent images and registered to CE-2 DOM. Local DEM and DOM with 0.02 m resolution were produced routinely at each waypoint along the rover traverse. The lander location was determined to be (19.51256°W, 44.11884°N, 2615.451 m) using a method of DOM matching. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 20 publications
0
88
0
1
Order By: Relevance
“…As an example, if rock depth increases from 3.0 to 4.0 m, the 11% relative error caused by a 20% uncertainty in antenna height would reduce to 8%. High‐resolution topography data generated from CE‐3 landing camera show that the landing site is relatively flat, with a slope generally less than 5° (Liu et al, ). Therefore, it is expected that surface slope would not produce any significant error in the estimated relative permittivity.…”
Section: Methodsmentioning
confidence: 99%
“…As an example, if rock depth increases from 3.0 to 4.0 m, the 11% relative error caused by a 20% uncertainty in antenna height would reduce to 8%. High‐resolution topography data generated from CE‐3 landing camera show that the landing site is relatively flat, with a slope generally less than 5° (Liu et al, ). Therefore, it is expected that surface slope would not produce any significant error in the estimated relative permittivity.…”
Section: Methodsmentioning
confidence: 99%
“…After removing the topographic signature, which is less than 2 m in elevation differences along Yutu's path [Liu et al, 2015], the thicknesses ( Figure 4) and depths ( Figure 5) of the strata were calculated from depths of prominent reflectors (e.g., interface I in Figure 2) at all reboot locations. A continuous distribution of thicknesses and depths was estimated using kriging interpolation.…”
Section: The 3-d Geological Modelingmentioning
confidence: 99%
“…They found that the candidate landing area was relatively flat, with a slope of less than 15°. Liu et al (2015) presented a method for high-precision topographic mapping with multi-source data. Analysis of the geomorphology surrounding the CE-3 landing site shows that the landing area and its surroundings are typical lunar mare with flat topography .…”
Section: Study Area and Datamentioning
confidence: 99%